OPTIMIZATION OF WHEAT DOUGH RHEOLOGY AND BREAD QUALITY THROUGH THE ADDITION OF FLAXSEED FLOUR (Web of Technology: Multidimensional Research Journal, 2025)
The study investigates the impact of flax (linseed) flour on the rheological properties of wheat dough and the quality of bread produced using various technological methods. Incorporating flax flour at a level of 10% resulted in a 3% increase in the specific volume of the product and improved organoleptic quality compared to samples with 7% flax flour.Utilizing natural additives derived from domestic raw materials including wild-harvested sources and by-products from food processing enterprises enables the production of bakery products with enhanced nutritional value while offering significant economic benefits. The inclusion of these additives reduces the consumption of primary raw materials in the formulation of national bakery products, such as varietal wheat flour and solid animal fats.For this study, simple and enriched Uzbek flatbreads were produced using rose hips and peanut seeds (deformed, crushed, or unsold), as well as partially defatted flax seeds (cakes). These raw materials, despite their high nutritional value, are often used for animal feed or discarded. The incorporation of these additives in the production of national bakery products provides tangible benefits by lowering material and production costs, reducing the consumption of flour and fat, and increasing the yield of finished products.